They Shall Expel Demons What You Need to Know About Demons - Your Invisible Enemies - Prince, Derek (Sout Pacific Derek Prince Ministries, 1998)
What are demons? How do demons gain entry into people's lives? Do Christians ever nee deliverance from demons? In this readable, biblically based book, Derek Prince answers these and many other vital questions. If you are struggling with problems that never seem to go away, has it ever occurred to you that demons may be at work? Or perhaps you want to help others with such problems. Derek Prince points out that "Jesus never sent anyone out to preach the Gospel without specifically instructing and equipping them to take action against demons in the same way that He Himself did." If this is not true today, Prince asks, "Who has change? Jesus? The demons? The Church?" --
Keywords: Exorcism. Spiritual warfare. Demonology